(untitled) (Revista Espinhaço, 2014)
The paper presents the big Census figures about matters which afflict great part of the Brazilian population. The study shows a significant and general unemployment reduction in the country, with a formal employment proportion growth, followed by a relative fall of São Paulo labor force participation in national formal occupation, salaries and the VAF, what has motivated the investigations of social and spatial impacts of this economic deconcentration process throughout the medium-size Brazilian cities. It is observed that in those cities the displacement time spent on the home-job way is relatively smaller, and so we have estimated the additional payment values if the forced costs of this displacement were to be remunerated by the mean income value. Results show a contrast between the two prominent spaces (São Paulo Metropolitan Area and medium-size cities) and bring up the urgency of a high-quality public transportation in all current Brazilian main cities.